Co-inoculation of Bacillus subtilis and Bradyrhizobium liaoningense increased soybean yield and improved soil bacterial community composition in coastal saline-alkali land - He, Caizhi; Gao, Tongguo; Wang, Xinxin; Chen, Renqiang; Gao, Huiyan; Liu, Hongquan (Frontiers in Plant Science, 2025)
Saline-alkali land is an important reserve cultivated land resource, and increasing soybean yield in it is significant for food security. As soybean is sensitive to saline-alkali stress, planting it in such soil often causes problems like blocked root development and yield decline. In this study, field experiments were carried out in coastal saline-alkali land in Huanghua City, Hebei Province. Jidou 12 with strong saline-alkali tolerance was selected, and four treatments (CK:conventional fertilization;T1:conventional fertilization + 75L/hm2Bacillus subtilis 8–32 agent; T2:conventional fertilization + 75L/hm2Bradyrhizobium liaoningense CCBAU05525;T3:conventional fertilization + 75L/hm2Bacillus subtilis 8–32 agent and 75L/hm2Bradyrhizobium liaoningense CCBAU05525). Through data analysis, the effects of co-inoculation of Bacillus subtilis and Rhizobium on soybean yield, soil properties, enzyme activity and bacterial community composition were studied. The results showed that T3 significantly increased soybean yield to 3182.67 kg/hm2, with yield, grains per pod and 100-grain weight increasing by 18.03%, 18.6% and 2.7% respectively compared with CK. The pH, electrical conductivity and total water-soluble salt content of rhizosphere soil decreased by 2.8%, 11.0% and 5.4%, while water and organic matter content increased by 5.6% and 11.6%. The activities of alkaline phosphatase, sucrase, urease and catalase increased by 14.9%, 22.4%, 15.1% and 5.2%. Co-inoculation increased the relative abundance of Sphingomonas. There was no significant difference in the Ace and Chao indices, indicating no significant difference in OTU number. The Shannon index of T1 was lower, meaning lower bacterial community species diversity. Co-inoculation improved plant stress resistance by enhancing the rhizosphere soil environment, regulating the microbial community structure and soil salinity, promoting soybean yield formation. It provides a theoretical basis for scientific fertilization and soil improvement in saline-alkali soybean planting.